2015
DOI: 10.1111/ajps.12217
|View full text |Cite
|
Sign up to set email alerts
|

Veto Rhetoric and Legislative Riders

Abstract: Riders to appropriations bills have long been a favorite congressional instrument for forcing presidents to accept unwanted policies. To resist unwanted riders, presidents have increasingly resorted to veto threats. Are such threats credible, and do they influence legislation? To answer these questions, we analyze the legislative histories of hundreds of threatened and unthreatened riders from 1985 through 2008. We find that threats are effective in bringing the final legislation closer to the president's pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…More directly, presidents can offer legislative proposals (Bond and Fleisher, 1990; Eshbaugh‐Soha, 2005; Gelman, Wilkenfeld, and Scott Adler, 2015; Rudalevige, 2002) or advocate for their preferred legislative outcomes within Congress during deliberation (Beckmann, 2010). Presidents may also utilize veto threats in an effort to extract concessions from Congress (Cameron, 2000; Hassell and Kernell, 2016).…”
Section: Presidents and Lawmakingmentioning
confidence: 99%
See 2 more Smart Citations
“…More directly, presidents can offer legislative proposals (Bond and Fleisher, 1990; Eshbaugh‐Soha, 2005; Gelman, Wilkenfeld, and Scott Adler, 2015; Rudalevige, 2002) or advocate for their preferred legislative outcomes within Congress during deliberation (Beckmann, 2010). Presidents may also utilize veto threats in an effort to extract concessions from Congress (Cameron, 2000; Hassell and Kernell, 2016).…”
Section: Presidents and Lawmakingmentioning
confidence: 99%
“…There are good reasons, though, to suspect a president will, under certain conditions, make multiple public statements on a single piece of legislation. If, for example, presidents use veto threats to engage in sequential communication or bargaining with Congress (Hassell and Kernell, 2016; Cameron, 2000), it follows that presidents will make more than one public statement on a bill.…”
Section: Frequency and Timing Of Presidential Position‐takingmentioning
confidence: 99%
See 1 more Smart Citation
“…She found that “presidents sometimes provide Congress advance notice of their constitutional concerns [in SAPs], while at other times, they blindside Congress with concerns raised for the first time” in signing statements (Rice , 704). Hassell and Kernell () examined whether the president can use veto‐threat SAPs to limit riders to appropriations bills and found that such threats do help bring appropriations closer to the president’s preferences. Bonett and Kernell () use SAPs to estimate presidents’ ideologies and find that presidents are less extreme ideologues during unified government than CQ support scores suggest.…”
Section: Ppp Omb Logs and Saps As Measures Of Presidents’ Legislatimentioning
confidence: 99%
“…Early evidence suggests that presidents’ growing reliance on veto threats is well justified. Presidents have succeeded in knocking about half of the objectionable provisions out of both appropriations (Hassell and Kernell ) and authorization bills (Gunther and Kernell forthcoming).…”
mentioning
confidence: 99%